The assessment of functional capacity of institutionalized elderly in Maceió - AL - doi:10.5020/18061230.2010.p168 - Juliana Fonseca Pontes Barros; Kelly Cristina Araújo de Oliveira Alves; Almir Vieira Dibai Filho; José Erickson Rodrigues; Hetelvina Carvalho Neiva (Universidade de Fortaleza, 2012)
Objective: To assess, by means of Katz Index, the functional capacity of institutionalized elderly in relation to their basic activities of daily living. Methods: We conducted a quantitative and cross-sectional study in a sample of 62 institutionalized elderly of both genders, from the House of the Poor of Maceió, Alagoas, with a mean age of 77.03 ± 7.77 years, with different levels of functionality, being emphasized activities related to self-care. Individuals initially classified as independent, partially dependent and fully dependent, were reclassified regarding functional dependence according to the score of the Katz Index. Results: There was a setback in the functional capacity of elderly in all functions assessed by the Katz Index, being more evident at older ages. Conclusions: We observed in this study, by applying the Katz Index that, in accordance with advancing age, there is a setback in the functional capacity of elders. Moreover, we confirmed the presence of functional dependency even in younger subjects, which showed the deficit of the functions in institutionalized elderly. NCT00895856